Credit analysis in banks with reference to Bank Bumiputra Malaysia Berhad / Abdul Rashid Rahim - Rahim, Abdul Rashid (1993)
Non - performing loans have been mounting on bank balance sheets during 1990s. The huge number of bad debts seems to reflect a clear decline in the banking community ability to assess credit worthiness accurately. The theories behind lending are well established but banks seemed to break down. It is important to know how banks deal with credit analysis which is the important activity in the lending process. The purpose of credit analysis is to assess the borrower's ability to repay a loan from normal asset conversions or from normal operating cash flows. Credit analysis focuses on two issues that are whether the customer can repay a loan and whether the customer will repay the loan.